New Results on Brain Stimulation in Chronic Pain - Antal, Andrea; Paulus, Walter; Rohde, Veit (Neurology International Open, 2017)
Pain that has become chronic has lost its warning function and is associated with dysfunction of the so-called pain network. Systematic brain stimulation aims to normalize this network by modulating neuronal activities. Non-invasive DC stimulation (tDCS) or repetitive transcranial magnetic stimulation (rTMS) are considered effective in pain treatment. Here, the stimulation of the primary motor cortex (M1) plays a central role. If the pain is not adequately controlled by tDCS and rTMS, invasive procedures such as motor cortex stimulation (MCS) or deep brain stimulation are available as a last resort.
Keywords: tDCS; transcranial direct current; deep brain stimulation; chronic pain; neuromodulation